Intracellular modelling and control of HIV-1 kinetics, T-lymphocyte decline and Immuno- senescence - Ssebuliba, Joseph (Stellenbosch : University of Stellenbsoch, 2010)
Thesis (MSc (Mathematical Sciences))--University of Stellenbosch, 2011.